PERANCANGAN DAN ANALISIS PEMBANGKIT LISTRIK TENAGA SURYA KAPASITAS 10 MW ON GRID DI YOGYAKARTA - Sigit Sukmajati; Mohammad Hafidz (Energi & Kelistrikan, 2015)
Solar energy (solar) provides many benefits to human life. One of the utilization of solar energy that can be done is in the form of Solar Power Generation (PLTS). In this thesis will design of a solarcell power system with a capacity of 10 MW on-grid with location in Yogyakarta. Performance solar cell power system 10 MW on-grid simulated using software RETScreen Clean Energy ProjectAnalysis Software, which was designed by Natural Resources Canada. The project began with a prefeasibility study of the solar cell power system 10 MW on-grid using RETScreen software that hasan extensive database of meteorological data including daily global horizontal solar radiation and also databases of various components of renewable energy systems from different manufacturers.Technical and financial performance of the solar cell power system 10 MW on-grid simulated using RETScreen software. Preliminary analysis of the simulation results show that this project is sociallybeneficial to the community. The draft is expected to be used as a model to develop a network of Solar Power System (PLTS).